(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Abstract Studies on madness, for different reasons, have mainly focused on women as the most affected group. In patriarchal societies, madness is associated with women as the challenge of the weak gender which cannot handle difficult situations. In The Official Wife, Okurut presents a female character with a frequency of madness resulting from her patriarchal marriage. Other female characters in the novel are not only driven into madness because of patriarchal subordination, but also the dilemma of the kinds of marriage that they are involved in. Through the clandestine marriage, male characters marry more than one wife secretly while they are officially involved in Christian marriage which discourages polygamy. Okurut presents the Ugandan society where Christianity is entertained as a form of civilization while the societal traditions including polygamy are embraced. In the narrative, Liz’s confusion and madness against the system is a representation of the real condition of the female characters who have failed to understand and accept the existing system which acknowledges Christian marriage and accepts polygamy at the same time.